Pencegahan anemia melalui edukasi dan pemberian suplemen di SMPN 1 kampar kiri hilir - Fadhli, Haiyul; Pratiwi, Amanda Putri; Khoiriah, Anisah; Wulandari, Venny; Maspat, Rinta; Ananto, Deswita Sandra Tsalsabila (Penerbit Goodwood, 2025)
Purpose: The objective of this program is to improve adolescents' knowledge about anemia and raise awareness about the importance of a healthy lifestyle, particularly focusing on preventing stunted growth in the future. Methodology: The program was conducted at SMPN 1 Kampar Kiri Hilir. The methods used included lectures and discussions, with the support of leaflets for information dissemination. Additionally, pretest and posttest evaluations were conducted to measure the change in knowledge among the participants. A total of 94 students took part in the activity. Results: The program resulted in a significant improvement in students' knowledge about anemia, as shown by the increase in the average posttest score (85.11%) compared to the pretest score (61.7%). The socialization also raised awareness about the importance of taking blood supplement tablets to prevent stunting. Conclusion The socialization program was effective in improving adolescents' understanding of anemia, including its symptoms, causes, and prevention methods. Limitation: This study is limited to a single school with a homogeneous sample, without evaluating external factors or the long-term impact on behavioral changes and students' health status. Contribution: This program successfully improved students' knowledge about anemia through a school-based educational approach and supported efforts to prevent anemia and stunting among adolescent girls.